Leaching behavior of fluorescent additives from microplastics and the toxicity of leachate to Chlorella vulgaris - Luo, Hongwei; Xiang, Yahui; He, Dongqin; Li, Yu; Zhao, Yaoyao; Wang, Shuo; Pan, Xiangliang (The Science of the total environment, 2019)
Chemical additives leaching from microplastics and their effects on physiology of microalgae are of environmental significance. So far, these issues remain unclear. Here, the leaching behavior of fluorescent additives from polyurethane sponge microplastics in simulated (acidic, saline, and basic water) and natural waters (river, lake, wetland, and sea water) was investigated. Release amount of additives increased with increasing solution pH and leaching time. The maximum release amount was reached at the leaching time of 12–24 h and the 3,3′-diaminobenzidine-like substances were identified in the leachate. The leached concentrations of fluorescent additives in simulated and natural waters followed the order of basic water > saline water > seawater > West Lake > River > Wetland. Effects of leachate and microplastics on growth and photosynthesis of Chlorella vulgaris were further evaluated. The maximum quantum efficiency of photosystem II (Fv/Fm) decreased with increasing leachate concentrations. Only high content (1.6 g L−1) of microplastics exerted significant inhibitory influence on cell photosynthesis when microalgae were exposed to microplastics alone. Retention of algal cells inside the porous sponge microplastics did not change their photosynthetic efficiency. These findings indicate that leaching process of additives from microplastics depends mainly on water environments and the leached chemicals may pose ecological risks to aquatic organisms. [Display omitted] •Release amount of additives increased with increasing solution pH and leaching time.•Different leaching patterns of additives in simulated and natural waters were observed.•The photosynthetic efficiency decreased with increasing leachate concentrations.•Retention of algal cells in microplastics did not change their photosynthetic efficiency.